2011
DOI: 10.1080/0735648x.2011.554746
|View full text |Cite
|
Sign up to set email alerts
|

Probation officers' recommendations and final sentencing outcomes

Abstract: Using the focal concerns perspective, the current study examines the factors that affect probation officers' recommendations and the effect these recommendations have on final sentencing decisions. Results indicate that there is a high level of agreement between probation officers' recommendations and final sentencing decisions. When judges depart from recommendations, departures are most often upward, with judges sentencing defendants to a harsher penalty. Although it was predicted that the variables that con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
(25 reference statements)
1
5
0
Order By: Relevance
“…It may also relate to concerns about public safety based on discretionary probation officer judgments about risk, anchored in offense-based judgments rather than actuarial calculations. These impulses are consistent with the relevance of the focal concerns of “blameworthiness” and “dangerousness” as highlighted in some prior probation research (Freiburger & Hilinski, 2011; Harris, 2009; Leiber et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…It may also relate to concerns about public safety based on discretionary probation officer judgments about risk, anchored in offense-based judgments rather than actuarial calculations. These impulses are consistent with the relevance of the focal concerns of “blameworthiness” and “dangerousness” as highlighted in some prior probation research (Freiburger & Hilinski, 2011; Harris, 2009; Leiber et al, 2018).…”
Section: Discussionsupporting
confidence: 86%
“…Drass and Spencer (1987) provide evidence that, in classifying and responding to clients, probation officers apply a generic working client typology, anchored in their organizational and peer group setting. In a similar fashion, scholars have concluded that enforcement decisions among community corrections officers are made with reference to “focal concerns” (Freiburger & Hilinski, 2011; Harris, 2009; Kras et al, 2019; Leiber et al, 2018; Steffensmeier & Demuth, 2000; Steiner et al, 2011). The perspective sees decisions as expediently based on attributions concerned with a client’s: “blameworthiness” interpreted from their offense characteristics, “dangerousness” interpreted from their use of violence, criminal history and demographics, and “practical constraints,” anchored in relationships with other court actors (Richardson, 2015; Steffensmeier & Demuth, 2000).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Prior research finds that racial disparities in sentencing are decreased by educational attainment, suggesting that education may insulate offenders from the effects of racial bias (Franklin 2017). Similarly, Freiburger and Hilinski (2011) found that race affected probation officers' recommendations indirectly, partly via education levels. In our results, both rehabilitation variables were significant predictors for parole grants in the expected direction, which aligns with previous work on rehabilitation's role in parole decisions (see, for example, Ruhland et al 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Using data from Michigan, Freiburger and Hilinski (2011) find that sentencing outcomes were influenced more by race than probation officer recommendations. Other studies using data from Florida find that non-White offenders were 6 to 8 times as likely as White offenders to receive custodial sanctions (Warren, Chiricos, & Bales, 2012), and non-White offenders disproportionately receive habitual-offender status (Crow & Johnson, 2008).…”
Section: Racial/ethnic Disparity In State and Federal Sentencingmentioning
confidence: 98%